Otoritas Logos Alkitab Dalam Dekonstruksi Derrida dan Solusi Epistemologis Kesaksian Roh Kudus Bavinck - YK, Febri Krisopras; Fitriani, Kristiana (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This study critically analyzes the dialectical encounter between Jacques Derrida’s Deconstruction of the Biblical Logosentrisme and Herman Bavinck’s Internal Witness of the Holy Spirit (ITHS) as the decisive epistemological solution. Derrida’s critique, centered on différance (the deferral of linguistic meaning), exposes the text’s vulnerability at the level of human language, consequently fostering skepticism and hermeneutical relativism in the postmodern era. Utilizing a qualitative, dogmatic-philosophical method, this research argues that while Derrida's analysis accurately reflects the limitations of fallen human reason, it is ultimately rendered irrelevant to the believer. ITHS functions as a supranatural act of illumination, strategically shifting the anchor of certainty from the vulnerable object (the text) to the sovereign action of the Holy Spirit. The Spirit effectively bridges the différance gap, implanting an autoptistic and certain conviction regarding the Logos's authority. This synthesis supports presuppositional apologetics, establishing ITHS as the primary warrant that safeguards the Biblical Logos as the final and binding truth against contemporary relativism.